Estudo cinético da proteína dissulfeto isomerase: nitróxidos como reguladores da atividade catalítica - Oliveira, Altamir Fernandes De (2010)
Protein disulfide isomerase (PDI, EC 5.3.4.1) belonging to the thioredoxin superfamily, is a thiol oxidoreductase that catalyzes the oxidation and reduction of thiols and intramolecular disulfide isomerization. This chaperone, such activity is dependent of cysteine located on the active sites, is present in the endoplasmic reticulum (ER) and / or plasma membrane of eukaryotic cells. Previous studies of the catalytic activity of PDI were performed using different pseudo-substrates, among them, the di-eosin-glutathione disulfide (Di-E-GSSG), described as a usefull tool for monitoring the disulfide reductase activity of PDI . In this work, the synthesis and chromatographic purification of Di-E-GSSG were performed and the purity of the probe was verified by high performance liquid chromatography (HPLC). The enzyme kinetics of the reductase activity of recombinant PDI isolated over Di-E-GSSG was studied, characterizing the main physicochemical parameters of the enzyme through the formation of the fluorescent monomer (λexc=521nm; λemi=542nm) eosin-reduced glutathione (E-GSH). The value of the Michaelis-Menten constant (Km) was found to be 520.5 ± 129.8 nM, the maximum velocity of catalysis (Vmáx) was determined as 1,637 ± 0.1526 nM.min-¹ and the catalytic constant (Kcat) found was 1.364 . 10-³.s-¹. Few chemical compounds able to inhibit catalytic activity of PDI were reported. Thus, to verify if stable free radical compounds display this activity were tested piperidine nitroxides as potential inhibitors of PDI. These compounds, which have antioxidant, anti-inflammatory and radioprotective properties are “scavengers” of different radical species, among them, thyil radicals. The nitroxide 4-hydroxy-2,2,6,6-tetrametilpiperidine-1-oxyl (Tempol) was a weak inhibitor of PDI reductase activity. However, three other nitroxides specifically synthesized for this study showed higher inhibition power, with a direct correlation between increasing the hydrophobicity of the chemical structures and inhibitory action. This ability was confirmed by assays with PDI found in human platelets, confirming the hypothesis that the nitroxides are candidates for new drugs to modulate cellular functions involving the PDI activity.